2018
DOI: 10.1111/jgs.15411
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Unstructured Electronic Health Record Data in Geriatric Syndrome Case Identification

Abstract: Claims and structured EHR data give an incomplete picture of burden related to geriatric syndromes. Geriatric syndromes are likely to be missed if unstructured data are not analyzed. Pragmatic NLP algorithms can assist with identifying individuals at high risk of experiencing geriatric syndromes and improving coordination of care for older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 43 publications
0
88
1
1
Order By: Relevance
“…One of the plausible implementations of frailty into clinical practice is to identify frail patients using electronic health record data. [85][86][87] In a UK study, Clegg et al developed the electronic Frailty Index (eFI) from 36 deficits, 88 based on the Frailty Index of cumulative deficit model. 17 The eFI was automatically populated from routinely collected data stored in the existing primary care electronic health record where general practitioners (GPs) list all patient diagnoses.…”
Section: Implications and Challenges For Health Care Policymentioning
confidence: 99%
“…One of the plausible implementations of frailty into clinical practice is to identify frail patients using electronic health record data. [85][86][87] In a UK study, Clegg et al developed the electronic Frailty Index (eFI) from 36 deficits, 88 based on the Frailty Index of cumulative deficit model. 17 The eFI was automatically populated from routinely collected data stored in the existing primary care electronic health record where general practitioners (GPs) list all patient diagnoses.…”
Section: Implications and Challenges For Health Care Policymentioning
confidence: 99%
“…While from a research perspective it would be ideal for most or all EHR data to be captured via structured fields, there are practical barriers to this, including physician resistance to SDES use [7] and lack of ability to capture contextual information [17,18]. Hence, EHR systems such as SCM generally have the ability to capture unstructured data as well.…”
Section: Structured Ehr Componentsmentioning
confidence: 99%
“…In the absence of routine assessment, these documentations tend to be inconsistently available or for a subset of patients in specific clinical contexts (e.g., after a fall event, hospitalization, or major surgery), which may not represent an individual's usual state of health. A recent study by Kharrazi et al 79) showed that the prevalence of geriatric syndromes was underestimated when only claims and structured EHR data were analyzed; natural language processing of unstructured EHR data substantially improved detection by 1.5-fold for dementia, 3.2-fold for falls, 18.0-fold for malnutrition, and 455.9-fold for lack of social support. While these findings are promising, the contribution of unstructured EHR data for case identification depends on the health information technology infrastructure and completeness of documentation by health care providers.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
“…While these findings are promising, the contribution of unstructured EHR data for case identification depends on the health information technology infrastructure and completeness of documentation by health care providers. 79) How to best combine clinical information with administrative claims data or structured EHR data requires further investigation.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%